2021
DOI: 10.1177/17085381211016150
|View full text |Cite
|
Sign up to set email alerts
|

Microarray profile of circular RNAs identifies hsa_circ_000455 as a new circular RNA biomarker for deep vein thrombosis

Abstract: Objects Deep vein thrombosis is a type of severe venous thromboembolism that can result in high mortality and morbidity. The expression alternation of circular RNAs (circRNAs) has been found in various diseases. However, the function of circRNAs in deep vein thrombosis still remains unknown. Method The blood samples of deep vein thrombosis patients and health control were selected, circRNA microarray was performed, and qPCR was used to verify the expression of circRNAs. Also, GO/KEGG analysis was performed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Lou et al ( 16 ) have found that hsa_circ_000455 is a new circRNA biomarker for DVT in patients, according to microarray profiling. Their findings have indicated that certain circRNAs can be used as indicators of DVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lou et al ( 16 ) have found that hsa_circ_000455 is a new circRNA biomarker for DVT in patients, according to microarray profiling. Their findings have indicated that certain circRNAs can be used as indicators of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies have shown that circRNAs are closely associated with the diagnosis and treatment of cardiovascular diseases, and certain circRNAs have been identified as cardiovascular disease biomarkers (11)(12)(13)(14)(15). Recently, circRNAs have been reported to accelerate lower extremity DVT via sponging miRNA, thus regulating mRNA expression (16,17). Although circRNAs have been suggested to be involved in the pathogenesis and regulatory mechanism of DVT, few studies have examined the global dynamic changes in circRNAs and mRNAs during DVT progression.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones may have non-genetic effects on the behavior of endothelial cells [17,18]. In a study regarding tumor thrombosis, Lou [19] found that 303 circular RNAs were differentially expressed in DVT using microarray. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the most significantly enriched pathways included thyroid hormone-signaling pathway and endocytosis, and also increased level of proteoglycans in cancer.…”
Section: Introductionmentioning
confidence: 99%